Beyond the veil, inc. assessing the viability of the one person corporation as tool for estate planning (Philippine Law Journal, 2022)
One of the major innovations introduced by the Revised Corporation Code of the Philippines is the One-Person Corporation (OPC) in our jurisdiction. This Note analyzes the viability of the OPC as a potential vehicle for estate planning. The use of corporations as a vehicle to facilitate the intergenerational transfers of wealth is founded on the application of corporation law principles to consolidate wealth for eventual transfer to heirs through the laws of succession. As the first unipersonal corporate form available to private citizens, the use of the OPC as a vehicle for estate planning requires an examination of its applicability for this purpose, as well as the potential challenges such use may face vis-à-vis the existing legal framework of succession. Using official documents of the Philippine legislature, jurisprudence from foreign jurisdiction and other documents, this Note discusses the development of the concept of the unpersonal corporation, its benefits, and potential challenges.